Suggestive loading of quotations in newspaper language - Holtvian, Valentyna; Severenchuk, Iryna (Видавництво Львівської політехніки, 2017)
The article focuses on the analysis of quotations as a pervasive and a persuasive feature of news text and the instrument of suggestion which may significantly determine the way readers perceive media information.
Keywords: news discourse; direct and indirect quoting; suggestion; impression; insinuation; public opinion and attitude